Seismic Anisotropy in the Northern Sumatra Region from Shear Wave Splitting - Arya Dwi Chandra; Bagus Jaya Santosa (Institut Teknologi Bandung, 2022)
The northern Sumatra consists of several tectonic segments, such as subduction zone, the Sumatra and Mentawai faults. An analysis that can be used to identify the tectonic segments, located beneath the northern Sumatra, is shear wave- splitting. The purpose of the analysis of shear-wave splitting is to monitor the anisotropic characteristics of the structure of the earth layers located beneath the northern Sumatra. The monitoring data were collected from 4 BMKG stations with the magnitude was more than 6.3 Mw and the the range of the epicentral distance was about 85̊-140̊. The data analysis was conducted by using Splitlab program based on rotation-correlation method. The result of the shear-wave splitting analysis shows that there are two anisotropic layers. The delay time found in the first layer is about 0,5-0,9 s, which is assumed that it occurs due to the Sumatran fault. Meanwhile, the delay time found in the second layer is about 1,4-1,8 s, which is assumed that it occurs due to the subduction plate movement on the upper mantle layer. The results of TPTI, TSI and TRSI stations has shown congruence, that is the polarization direction is parallel to the Sumatra fault on the upper layer and the polarization direction is perpendicular to the Sumatra fault on the lower layer. The PSI station shows the polarization direction is different from the other stations, in which they show the polarization direction is perpendicular to the Sumatra fault on the upper layer and the polarization direction is parallel to the Sumatra fault on the lower layer. The difference of the data processing in the PSI station, we assume, is caused by the presence of a complex layer beneath Toba caldera.